2020
DOI: 10.24252/al-kimia.v8i1.12173
|View full text |Cite
|
Sign up to set email alerts
|

Modified CaO Catalyst from Golden Snail Shell (Pomacea canaliculata) for Transesterification Reaction of Used Cooking Oil

Abstract: One of alkaline earth metal oxide is calcium oxide, CaO has more attention because it has high strength, low solubility in methanol, and can be synthesized from sources that are easy to obtain. One of the sources of CaO and showed its catalytic properties was the golden snail shell. In this study, synthesize ash golden snail shell modified with fly ash leached and non-leached as a source of silicate (SiO2) has been investigated. The CaO/fly ash catalyst was applied to the transesterification reaction of used c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The CaO absorption appeared under 600 cm -1 [4], which was seen at 454 cm -1 in current study. Furthermore, the absorption of CaCO3 did not appear in the wavenumber of 1800 -800 cm -1 , showed that the CaCO3 from snail shell has been perfectly decomposed to form CaO, see Equation 3 [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CaO absorption appeared under 600 cm -1 [4], which was seen at 454 cm -1 in current study. Furthermore, the absorption of CaCO3 did not appear in the wavenumber of 1800 -800 cm -1 , showed that the CaCO3 from snail shell has been perfectly decomposed to form CaO, see Equation 3 [9].…”
Section: Resultsmentioning
confidence: 99%
“…The shells were crushed and washed to remove impurities. Furthermore, the shell was dried in the oven at 110 C for 24 hours followed by calcined at 900 C for 2 hours to obtain the shell powder [9]. In order to determine the presence of CaO functional group and the crystalline phase, the catalyst was analyzed using FT-IR-ATR Bruker Alpha equipped with diamond crystal.…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, an oxide support material namely CaO from calcined golden snail shells was added to nanoparticles. The calcination process is carried out at high temperatures to activate the catalyst and to decompose the carbonate groups into CaO [7].…”
Section: The Synthesis Of Cao-mnfe2o4 Nanoparticlesmentioning
confidence: 99%
“…CaO is semiconductor material that had a specific crystal size and surface area so it has good catalytic activity [5], [6]. CaO could be produced from environmentally friendly materials containing calcium carbonate such as golden snail shells that potential as catalyst [7].…”
Section: Introductionmentioning
confidence: 99%